Pengaruh Model Project Based Learning Berbasis STEAM terhadap Hasil Belajar Peserta Didik pada Materi Transformasi Energi Kelas IV di SDN 36 Banda Aceh - Intan Syaravina; Nurmasyitah Syitah; Intan Safiah (Pesona Dasar : Jurnal Pendidikan Dasar dan Humaniora, 2023)
ABSTRACTThe problems in this study relate to importance of choosing a learning model. A good learning model can be used to make the teaching and learning process more effective, meaningful and pleasantly. The research used to know students will get learning outcomes that can meet the KKM. And the fact of this research is teaching and learning in class is still not optimal in using learning models. Based on these problems need an update. One of the meaningful, effective, and fun learning alternatives that can be applied in developing student competencies is to use the STEAM-based project based learning model. The formulation of the problem in this study is "Does the STEAM-based project-based learning model affect student learning outcomes in class IV energy transformation material at SDN 36 Banda Aceh". The purpose of the research was to determine the effect of the STEAM-based project based learning model on student learning outcomes in class IV energy transformation material at SDN 36 Banda Aceh. This study uses a quantitative approach. The population in this study were all students of SDN 36 Banda Aceh while the samples were all students of class IV, totaling 30 people. Data collection techniques used tests, while data analysis techniques used normality tests and to test hypotheses using paired sample t. From the results of hypothesis using t-test the significance value (2-tailed) on the test was 0.000 0.05, where the average value of the learning test results was 85.5. So it can be concluded there is an influence of the STEAM-based project-based learning model on student learning outcomes in energy transformation material.Keywords: Project Based Learning Model, Energy Transformation, Learning Outcomes.